In Vitro Antibacterial Activities of Selected Medicinal Plants Against Diarrhoea Causing Pathogens - Saadu, Murtala; Kuta, Faruk Abubakar; Muhammed, Hadiza Lami; Wuna, Mohamed (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Diarrhea has been a major cause of death, especially among children in developing countries. Traditional preparations of medicinal plants with antimicrobial activities have been extensively used in West African regions. This study was conducted to determine the antibacterial activities of selected medicinal plants against pathogens that cause diarrhea. Fresh leaves of three medicinal plants, namely Anogeissus leiocarpus, Vernonia amygdalina, and Piliostigma thonningii, were collected in Minna, Niger State. Pathogens causing diarrhea (Vibrio cholerae, Klebsiella pneumoniae, and Salmonella enterica serovar) were isolated and identified from stool samples of individuals suffering from diarrhea. The plant material was extracted using the maceration technique with methanol. The antibacterial effectiveness of the selected plant extracts was evaluated using the agar well diffusion method on Muller Hinton agar. The minimum inhibitory concentration was determined using the Broth tube dilution method, while the minimum bactericidal concentration was determined by plating out on nutrient agar plates with no visible growth. The results indicated that all plant extracts effectively suppressed the microbial growth of diarrhea-causing bacteria with varying potency. Among them, the extract of Anogeissus leiocarpus consistently exhibited the largest inhibitory zone diameters across all three bacterial strains at a concentration of 300 mg/mL (Vibrio cholerae: 32.33 mm, Klebsiella pneumoniae: 34.00 mm, and Salmonella enterica serovar Kentucky: 36.33 mm). This extract can be considered the most active. For Anogeissus leiocarpus, the MIC values ranged from 0.19 to 0.96 mg/mL, and the MBC values ranged from 0.20 to 1.09 mg/mL. For Vernonia amygdalina, the MIC values ranged from 0.96 to 1.80 mg/mL, and the MBC values ranged from 1.20 to 1.920 mg/mL. The results of this study validate the traditional use of these plants in medicine. However, further studies, including the isolation and identification of active compounds would be necessary to fully understand the mechanisms behind the observed antimicrobial effects.